A Structural Equation Model of Depression Risk in Young Women with a History of Child Sexual Abuse - Cantón-Cortés, David; Cortés, María Rosario; Cantón, José; Cortés, María Rosario (My University, 2021)
This study aimed to propose and empirically test a model of the role of beliefs and emotions, self-destructive coping, and anxious attachment in the etiology of depression among a sample of 217 female survivors of child sexual abuse (CSA). The structural equation model showed a direct path from feelings of betrayal, self-destructive coping, and major anxious attachment to depression. The model also showed an indirect path (via self-destructive coping and anxious attachment) from feelings of powerlessness—particularly self-blame/stigma—to depression. The present results confirmed the existence of an explanatory model of depression risk in young adult women.
Keywords: Niños - Abusos sexuales; Depresión mental; Mujeres jóvenes; Child sexual abuse; Traumagenic dynamics; Depression